Photoelectrochemical properties of InN nanowire photoelectrodes for solar water splitting. (6th June 2016) - Kamimura, J; Bogdanoff, P; Ramsteiner, M; Geelhaar, L; Riechert, H
Abstract: InN nanowires were grown on Si(111) substrates by plasma-assisted molecular beam epitaxy. Raman spectroscopy showed that the nanowires were strain-free and allowed the deduction of a free carrier concentration of 1–2 × 10 18 cm −3 . This value was confirmed by a Mott–Schottky analysis of electrolyte-based capacitance-voltage measurements. In addition, these measurements directly revealed the existence of a surface accumulation layer in the InN nanowires. In cyclic voltammetry measurements under irradiation from a Xe lamp with about 100 mW cm −2, high photocurrents of about 4 and 11 mA cm −2 were observed at 1.23 and 1.63 V bias potential versus reversible hydrogen electrode, respectively, using H2 O2 as a hole scavenger. By comparing the photocurrent with and without H2 O2, the main limiting factor in the performance of InN nanowire photoanodes was identified to be the poor catalytic efficiency for water oxidation at the surface, followed by parasitic bulk recombination.